2017
DOI: 10.1038/s41430-017-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whole milk compared with skimmed milk on fasting blood lipids in healthy adults: a 3-week randomized crossover study

Abstract: Intake of 0.5 L/d of whole milk did not adversely affect fasting blood lipids, glucose, or insulin compared to skimmed milk. Moreover, intake of whole milk increased HDL cholesterol concentration compared to skimmed milk. These findings suggest that if the higher energy content is taken into account, whole milk might be considered a part of a healthy diet among the normocholesterolemic population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 22 publications
3
18
0
1
Order By: Relevance
“…Likewise, previous MR analyses demonstrated genetically high milk intake also did not influence plasma concentrations of glucose (12,13 ). Our findings were also supported by a 3-week randomized crossover study indicating that both whole milk and skim milk did not affect fasting glucose or insulin in healthy adults (32 ). Our MR results may potentially explain the nonsignificant causal effect of high milk intake on risk of type 2 diabetes (11 ).…”
Section: Discussionsupporting
confidence: 79%
“…Likewise, previous MR analyses demonstrated genetically high milk intake also did not influence plasma concentrations of glucose (12,13 ). Our findings were also supported by a 3-week randomized crossover study indicating that both whole milk and skim milk did not affect fasting glucose or insulin in healthy adults (32 ). Our MR results may potentially explain the nonsignificant causal effect of high milk intake on risk of type 2 diabetes (11 ).…”
Section: Discussionsupporting
confidence: 79%
“…Our results showed that consuming whole dairy products does not increase the cholesterol/HDL ratio during six months of following this dietary advice, is in line with other reports [44,45]. Consumption of dairy products has been associated with a lower risk of mortality and major cardiovascular disease events in a diverse multinational cohort, without added risk by intake of whole fat dairy products [46].…”
Section: Discussionsupporting
confidence: 92%
“…However, a comprehensive review of Drouin-Chartier et al (59) assessed evidence from RCTs and reported no harmful effect of dairy consumption, irrespective of fat content, on different aspects of cardiometabolic risk. More recently, Engel et al (60) conducted a 3-wk crossover dietary intervention in 18 healthy adults to compare the effect of whole milk with skimmed milk consumption. The results showed that ingestion of 0.5 L/d whole milk did not adversely affect fasting glucose or insulin compared with skimmed milk.…”
Section: Evidence From Rcts On Dairy Products and T2d Riskmentioning
confidence: 99%